Innovating in university: a real alternative or always the same thing? - Chavez, Jorge; Jiménez, Felipe; Fauré, Jaime (Universidade Estadual de Maringa, 2021)
Research in the educational field on implicit theories suggests that the nature of innovations in university teaching contexts depends, to a large extent, on what theories teachers have constructed about what it means to learn, teach and innovate. Our main objective was to analyze the implicit theories of a group of twelve professors who presented innovation projects in a Chilean university. Following a qualitative approach, in-depth interviews were conducted with each of these teachers, who were responsible for the projects. Our results suggest that teachers conceive learning, teaching and innovation from a series of constructivist notions. However, at the moment of foreseeing the instructional design of their projects they fail on identifying the manner in which these aspects should be concretized in practice. We discuss implications of these results for both research and educational practices.
Inovar na universidade: uma alternativa real ou mais do mesmo?
Innovar en la universidad: ¿una alternativa real o más de lo mismo?
Keywords: Higher education.; Implicit theories.; Educational psychology.